Analysis of Green Products, Financial Technology, and Promotion on Sales Volume Increase at PT. Sinar Teknik Tirta Pratama: Analisis Green Product, Financial Technology dan Promosi Terhadap Peningkatan Volume Penjualan di PT. Sinar Teknik Tirta Pratama - Aurelia Vasly; Elisabeth Nainggolan (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
This investigate was incited by a decay in deals volume, as prove by the benefits earned by PT Sinar Teknik Tirta Pratama. This was due to the items sold by PT Sinar Teknik Tirta Pratama being seen as hurtful to the environment, inadequate installments, and incapable advancement, all of which influenced the company's benefits. The objective of this think about is to analyze deals volume through green items, budgetary innovation, and advancement in the chlorine industry. The strategy utilized in this consider is a quantitative strategy utilizing essential information sources. The data will be analyzed through quantitative clear examination gotten utilizing a survey conveyed to respondents, and this consider is measured utilizing a Likert scale to get conclusions. The testing method utilized is irregular examining. At that point, the information collected related to the investigate protest is analyzed based on the respondents' reactions gotten utilizing the Hair et al. equation. The theory in this think about is tried utilizing different direct relapse investigation. The comes about appear that budgetary innovation, green items, and advancements have a critical impact on deals volume.